Hepatocellular Carcinoma Metastasis to the Orbit in a Coinfected HIV+ HBV+ Patient Previously Treated with Orthotopic Liver Transplantation: A Case Report. (20th December 2011) - Guerriero, S.; Infante, G.; Giancipoli, E.; Cocchi, S.; Fiore, M. G.; Piscitelli, D.; Cardascia, N.
Abstract : Hepatocellular carcinoma rarely metastasizes to the orbit. We report a 45-year-old male, HBV+, HIV+, with a past history of a liver transplant for ELSD (end-stage liver disease) with hepatocellular carcinoma and recurrent HCC, who presented with proptosis and diplopia of the left eye. CT scans of the head revealed a large, irregular mass in the left orbit causing superior and lateral destruction of the orbital bone. Biopsy specimens of the orbital tumor showed features of metastatic foci of hepatocellular carcinoma. Only 16 other cases of HCC metastasis to the orbit have been described in literature, and this is the first case in a previously transplanted HIV+, HBV+ patient.